Profile of High School Science Learning and the Potential for Implementation of Design Based Learning in Learning During the Covid Period - Arie Novia Santi*; Anna Permanasari; Didit Ardianto (Universitas Syiah Kuala, 2021)
Science teachers must be able to design learning to be able to accommodate demands 21st century learning. Therefore, a study was conducted that aims to analyze the profile of learning with DBL in high school science learning. The research method used is descriptive qualitative method based on learning outcomes through information learning interviews conducted with teachers at the MA Boarding School As Sa'idah Sukabumi as many as 15 people. The results of the interviews showed that generally science teachers had apply the learning process with PBL, PjBL, and discovery learning models by using Process Approach, inquiry and concept. However, students have not demonstrate quality interactions to build critical thinking in accordance with which is expected. Furthermore, no teacher has implemented it yet STEM-based science learning. The results of interviews with teachers show 99% of teachers already familiar with STEM learning, but 65% have not applied it in learning. Meanwhile, the results of interviews with teachers found that DBL which is a marker of STEM learning has never been implemented in science class. Research result provide the need for science learning innovations using the approach DBL, given the highly prospective characteristics of DBL for establishing quality interactions, thinking, creative students and practice the ability to collaborate and communicate students, even in this Covid-19 pandemic situation